2019
DOI: 10.1108/jta-05-2018-0014
|View full text |Cite
|
Sign up to set email alerts
|

The instrumental time of memory: local politics and urban aesthetics in a tourism context

Abstract: Purpose This paper aims to show that tourism is one of the most perfect creations of the capitalist mode of production insofar as not only does it consume places and territories and perpetuate dependency relations, but in the expressive dimension, it also produces feelings and meanings and generates a new relationship of the past with the present and future (chronotope). Design/methodology/approach The study was carried out using a socio-anthropological approach with participant observation over several deca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(35 reference statements)
1
1
0
Order By: Relevance
“…The demonstrated cases of political corruption that have been echoed by the media in recent years for their economic, judicial and social significance are merely the tip of the iceberg of a problem hidden by many interested parties, and also due to the shortage of the means to fight it. Particularly for Spain, and in accordance with [69,74], political corruption emerged (more than 200 reported cases) during the economic boom between 2000 and 2011, while almost no local corruption was previously registered.…”
Section: Novelties Of the Study And The Paper's Structuresupporting
confidence: 53%
“…The demonstrated cases of political corruption that have been echoed by the media in recent years for their economic, judicial and social significance are merely the tip of the iceberg of a problem hidden by many interested parties, and also due to the shortage of the means to fight it. Particularly for Spain, and in accordance with [69,74], political corruption emerged (more than 200 reported cases) during the economic boom between 2000 and 2011, while almost no local corruption was previously registered.…”
Section: Novelties Of the Study And The Paper's Structuresupporting
confidence: 53%
“…Several studies have demonstrated that factors such as lifestyle, autonomy and self-fulfillment prevail among entrepreneurs in the tourism industry (Block and Landgraf, 2016; Andersson et al , 2002; Ateljevic and Doorne, 2000; Getz and Carlsen, 2000; Nilsson et al , 2003). Tourism is an industry of senses (Nogués-Pedregal, 2019), something that connects with the ongoing discussion on the methods used to measure entrepreneurial success, and include non-financial and even qualitative aspects (Rey-Martí et al , 2016). Some entrepreneurs start a business in a destination after they have experienced life there as a visitor (Muller, 2006; Williams and Hall, 2002; Williams et al , 2000).…”
Section: Quality Of Life or Profitabilitymentioning
confidence: 99%